2013
DOI: 10.1177/1473325013503003
|View full text |Cite
|
Sign up to set email alerts
|

‘Having housing made everything else possible’: Affordable, safe and stable housing for women survivors of violence

Abstract: Research indicates that the need for safe housing and the economic resources to maintain safe housing are two of the most pressing concerns among abused women who are planning to or have recently left abusers. Intimate partner violence (IPV) is frequently an immediate cause or precursor to homelessness and housing instability. The aim of the study is to explore abused women’s experiences accessing affordable, safe, and stable housing. To achieve the aim, adult female IPV survivors answered questions about: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 43 publications
3
54
0
4
Order By: Relevance
“…Other researchers have found similar findings, with women opting not to live in specific housing due to fear of their safety and their family's safety (Clough, Draughon, Njie-Carr, Rollins, & Glass, 2014;Lazarus, Chettiar, Deering, Nabess, & Shannon, 2011). This finding is an example of the gendered nature of poverty, where women are forced into homelessness due to safety concerns.…”
Section: Discussionsupporting
confidence: 55%
“…Other researchers have found similar findings, with women opting not to live in specific housing due to fear of their safety and their family's safety (Clough, Draughon, Njie-Carr, Rollins, & Glass, 2014;Lazarus, Chettiar, Deering, Nabess, & Shannon, 2011). This finding is an example of the gendered nature of poverty, where women are forced into homelessness due to safety concerns.…”
Section: Discussionsupporting
confidence: 55%
“…Unstable housing situations, which are common among trans populations in the United States, further affect survivors' ability to seek services or report cases of violence. Research among cisgender women has demonstrated that appropriate housing better positions GBV survivors to seek services and, when necessary and/or if desired, to end abusive relationships (Clough, Draughon, Njie-Carr, Rollins, & Glass, 2014). For trans people, violence may be perpetrated by family members residing in the same household.…”
Section: Challenges In Seeking Care Protection and Justicementioning
confidence: 99%
“…Housing that could be considered an asset had to be safe and affordable, with or without assistance from private or government agencies. Women who have experienced IPV face many barriers that lead to unstable housing, such as disruptions from the abuser causing problems with landlords or lack of resources from social service agencies (Clough, Draughon, Njie-Carr, Rollins, & Glass, 2014). Women in this study described losing houses due to abuser behavior or inability to pay, and difficulty finding housing in an urgent situation, such as leaving an abusive partner.…”
Section: Resultsmentioning
confidence: 99%